RANCANG BANGUN AUTOMATIC AUDIO FREQUENCY FOLIAR FERTILIZATION SEBAGAI TEKNOLOGI ALTERNATIF UNTUK MENINGKATKAN HASIL PRODUKTIFITAS TANAMAN - Firmansyah Fahrul; Sumayyah Hany; Mahendra Aditya Danang; Dwilaksana Dedi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Automatic Audio Frequency Foliar Fertilization is a technology that improves between the nutrients performed on plant leaves by giving the sensation of sound waves in plants. Automatic Audio Frequency Foliar Fertilization is technology device leaf fertilizer integrated with Sound waves which will run automatically, more practical and compatible. This technology device consists of two main devices of active speakers that will issue a sound with a certain frequency and sprayer fertilizer. The results of the tests that have been done to produce the sound frequency between 1200 Hz up to 1600 Hz with average noise of 5%, with the debit of nutrient spraying for the plant of 96 ml per 30 seconds. Giving exposure treatment Wave The sound of classical music with the provision of nutrients in mustard plants by Automatic Audio Frequency Foliar Fertilization gives a real effect on the growth of the average height of the plant is 2.14 cm per 2 days. Keyword : Automatic, Audio Frequency, Sparyer